Epidemiological and genomic analysis of the dengue virus isolate from Jeddah, Saudi Arabia: Implications for future therapeutic development - Shymaa Damfo; Eitezaz Abdulshakoor Zaki; Mohammed Yahya Marouf; Mohammed Abdulmajeed Alghamdi; Khader Saleh Alghamdi; Bader Mohammed Alqarni; Mona A. Almusawi (PLoS ONE, 2026)
Background Dengue fever is one of the major mosquito-borne diseases worldwide, and studies have shown that more than half of the world population could be at risk of dengue in the future. To date, there are no universally effective vaccines or specific antiviral treatments for dengue virus (DENV). Dengue fever has reported in the Western region of Saudi Arabia since 1994. A comprehensive understanding of the molecular epidemiology of the DENV in Saudi Arabia, with implications for therapeutic development, is still absent. Aim The present study aimed to integrate analysis of the circulating DENV genome and mutations of the most prevalent dengue serotype in the therapeutic context. Methods Retrospective data were used to conduct analysis of dengue infections in Jeddah city in Saudi Arabia from January to October 2024. All Saudis, non-Saudis, and Hajj and Umrah visitors with a confirmed diagnosis of dengue fever were included in the study. The demographic factors and DENV serotypes were explored. The genome of the most prevalent DENV serotype was sequenced using Oxford Nanopore Technology. Closely related strains were searched using the BLAST NCBI tool, and the NGPhylogeny server was used to analyze the phylogenetic relationship. In order to provide a biologically appropriate template for drug-design initiative, the dengue structural protein (prM) of an isolated strain was optimized through receptor modeling and mutation analysis using ICM tool. Results Analysis of the circulating DENV serotypes showed that higher incidence rates occurred in young adults, males, and from the Middle Eastern region of origin. The majority (95.3%) of confirmed cases were caused by the serotype DENV-2. A high nucleotide sequence identity was noted for strains originating from Pakistan (99.68%). Five ligands containing nitrogen-rich chemical scaffolds (piperidine, azoles, and sulfonamides) with a variety of substituents were identified by the study as possible binding hits to both wild-type and mutant prM receptor structures. Although of limited sample size and preliminary docking results, the epidemiological and molecular data generated in the study provide useful information for epidemic preparedness and possible therapeutic interventions.